Nilai-Nilai Pendidikan Islam dalam Estetika dan Spiritualitas Tarian Sufi - Aulia Nurhalizah; Maulida Hasanah; Mohamad Hafizh; Muthia Robiaturrifa (Lembaga Pengembangan Kinerja Dosen, 2025)
. This research aims to analyze the values of Islamic education that are internalized in the aesthetics and spiritual dimension of Sufi dance, especially in the Sema ritual. In the Islamic view, art is not only an expression of beauty, but also a means of da'wah and a manifestation of love for Allah the Most Beautiful (Al-Jamīl). Using the descriptive qualitative literature study method, this study examines the symbolic and spiritual meanings contained in each element of Sema. The results of the analysis show that Sema is a dynamic form of dhikr that is firmly rooted in the Sufism tradition, oriented towards the purification of monotheism, and the process of purification of the soul (tazkiyatun nafs). Aesthetic elements such as hirkah, tennure, and sikke costumes have a deep symbolism about ego release (fana'), while the rotating movement symbolizes a spiritual journey (suluk) towards oneness with God. Pedagogically, Sufi Dance contains the essential values of Islamic education, such as spiritual calmness, love, patience, and sincerity, which can be used as a holistic learning model to form the awareness of monotheism and spirituality of modern humans. This research confirms that spiritual arts such as Sema have significant relevance in contemporary Islamic education as a medium for internalizing transcendental values.